PERSEPSI MAHASISWA UNIVERSITAS RIAU TERHADAP PERAN TALKSHOW MATA NAJWA SEBAGAI LITERASI POLITIK - Diajeng Claudia Pahlawan; Sri Erlinda; Haryono Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The background of this research is motivated by the awareness that mass media as a part of an agent of political socialization which has an important role in the political field. In Indonesia, the fact is that television programs with political themes are growing, one of the leading talkshows is Mata Najwa. Mata Najwa talkshow has a content on politics and has a role as political literacy. The formulation of the problem in this study is how the Universitas Riau students’ perceptions toward the role of the Mata Najwa Talkshow as political literacy. The purpose of this research is to find out the perception of Universitas Riau students on the role of the Mata Najwa Talkshow as political literacy. The benefit of the research results is that it could become a source of learning for all parties, especially students and the mass media in terms of the ability to understand, analyze, and deconstruct the image or message content of the information released by the media and provide critical awareness for the audience when dealing with media content. This research method is descriptive quantitative, data collection instruments used in this study were questionnaires and interviews consisting of 9 indicators with 24 questions. The population in this study was students of the Universitas Riau. The sample in this study was taken using purposive sampling technique. Based on the result of the study, it was found that the result of the average percentage value of the alternative answers to the dominant respondents was 47.92% where this range was in the